(3GdeONd GdcHjQ Edi Yde GdQhMGfjGJs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s; (3Mfjf Hf GSMGb , CHh RjO Mfjf Hf GSMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3QH Jee hHGdNjQGJ Yee gPG GdcJGH GdeONd GdcHjQ Edi Yde CaYGd GdQhMGfjGJ ai GdeQcHGJ heG dgG ef GdJCKjQGJ s
(3BNQgG (B:s
(3GdaVi hGdedgi hGdHdhQ hGddDdD GdUZjQ hGdeQbTjfG hGdaVg GdHjVGA hGdedM GdCHjV hGdTH hGdLU hMLGQI GdcdS s
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B158 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs